The Interface between Inflammatory Bowel Disease, Neuroinflammation, and Neurological Disorders - Hey, Grace E.; Vedam-Mai, Vinata; Beke, Matthew; Amaris, Manuel; Ramirez-Zamora, Adolfo (Seminars in Neurology, 2023)
Inflammatory Bowel Disease (IBD) is a complex, chronic inflammatory condition affecting the gastrointestinal tract. IBD has been associated with a variety of neurologic manifestations including peripheral nerve involvement, increased risk of thrombotic, demyelinating and events. Furthermore, an evolving association between IBD and neurodegenerative disorders has been recognized, and early data suggests an increased risk of these disorders in patients diagnosed with IBD. The relationship between intestinal inflammatory disease and neuroinflammation is complex, but the bidirectional interaction between the brain-gut-microbiome axis is likely to play an important role in the pathogenesis of these disorders. Identification of common mechanisms and pathways will be key to developing potential therapies. In this review, we discuss the evolving interface between IBD and neurological conditions, with a focus on clinical, mechanistic, and potentially therapeutic implications.
Keywords: inflammatory bowel disease; Parkinson's disease; gut microbiome; brain–gut axis; ulcerative colitis; Crohn's disease